COMPARATIVE ANALYSIS OF ANTIOXIDANT ACTIVITY AND PHYTOCHEMICAL CONTENTS IN ETHANOLIC LEAF EXTRACTS OF IN VITRO AND FIELD GROWN WITHANIA SOMNIFERA - Jassal, Prabhjot Singh; Kaur, Gagandeep (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: The present study was planned to compare antioxidant activity in vitro and field grown Withania somnifera was assessed using 1, 1-diphenyl-2-picrylhydrazyl (DPPH) and nitric oxide (NO) assays. Medicinal plants are a major source of phytochemicals used for the treatments of human diseases. W. somnifera has anti-inflammatory, antioxidant, and antimicrobial properties. Methods: Antioxidant activity and phytochemical contents in W. somnifera were determined spectrophotometrically. Results: The results of antioxidant activity of field grown ethanolic leaf extract of W. somnifera showed maximum inhibition of 72.08% and 77.85% in DPPH (50 Î¼g/ml) and NO (100 Î¼g/ml) scavenging assays, respectively. Field grown ethanolic leaf extract of W. somnifera showed maximum concentrations of phenolics, flavonoids, and carotenoids, as active phytochemicals, determined spectrophotometrically, which were found as 676.5 Î¼g/ml, 557.5 Î¼g/ml, and 469 Î¼g/ml, respectively, as compared to in vitro plant extracts. Conclusions: This study demonstrated that antioxidant activity and phytochemical contents of field grown ethanolic leaf extract of W. somnifera were found to be comparatively higher than in vitro plant extracts. Leaf extracts of W. somnifera are a potential source of antioxidants and could prevent many free radical-related diseases. Keywords: Carotenoids content, 1-diphenyl-2-picrylhydrazyl scavenging assay, Flavonoids content, Nitric oxide radical scavenging assay, Phenolic content.